Moderasi Beragama dalam Perspektif Kementerian Agama Republik Indonesia: Konsep dan Implementasi - Haitomi, Faisal; Sari, Maula; Ain Binti Nor Isamuddin, Nor Farah (Al-Wasatiyah: Journal of Religious Moderation, 2022)
This paper aims to explain the concept of religious moderation promoted by the Ministry of Religion of the Republic of Indonesia which reaps the pros and cons in the public. One side agrees with the idea of ​​religious moderation because it is considered to be able of suppressing the flow of radical thought. However, on the other hand the rejection of this idea because it is considered a compromise of aqidah with people of different beliefs. This research is a descriptive literature review. The result of this study shows that it is important to present a moderate attitude in religion as promoted by the Ministry of Religion. This is one of the efforts to prevent radicalism and all forms of violence thatmake religion a scapegoat. With this principle, it is hoped that the stability of religious harmony as a whole will be maintained. Because the harmonization of one religion with different religion is what Rasulullah SAW wanted. Tolerance in religious life has actually been exemplified by Rasulullah SAW when migrated from Mecca to Medina by issuing the Medina charter, which stipulates the rules that must be obeyed by all residents of Medina regardless of the ethnicity, race, and religion.